Rancangan Pembuatan Program Perhitungan Packing Material Menggunakan Macro Excel pada PT Trias Sentosa - William Goentoro; Karina Agustin (Jurnal Titra, 2020)
Packing material calculation is an important things to be considered by the company. Company still uses a manual method to calculate packing material. Calculation program only calculate four type of packing material which is plywood, pallet, fitting and box. These four packing materials must be adjusted with the company products characteristics that makes these four packing materials have special calculation to increase productivity. Program was made using software called Macro Excel. Designing program provides convenience for company to minimize time and human error. This program also accompanied with a digital dashboard that give information about reorder point and economic order quantity of these four packing materials.